Enigmatic presence of rhyzoconcretion in Haliday Island in the Sundarbans, India: Geochemical insight - Supriyo Kumar Das; Dev Verma; Priyank Pravin Patel; Abhijeet Tripathi; Mainak Dutta; Dibyashree Mahapatra; Pravat Kumar Behera; Kaushik Gangopadhyay; Suchandra Mukherjee; Pankaj Kumar; Aritra Banerjee; Animesh Sinha; et al. (CATENA, 2026)

Edwardsiella ictaluri infection in farmed striped catfish Pangasianodon hypophthalmus in India - Chandra Bhushan Kumar; Tamal Seth; Devarshi Ranjan; Dev Kumar Verma; Naresh Kumar Sood; Neeraj Sood; Pravata Kumar Pradhan; Joykrushna Jena (Veterinary Research Communications, 2026)

Baicalein isolated from Oroxylum indicum acts as a potent µ- and κ-opioid receptor antagonist agent via the reversal of agonist-mediated cAMP inhibition - Kishan Singh; Anubhav Yadav; Sana Khan; Arti Shukla; Maksood Alam; Ashutosh Kumar Verma; Neerja Tiwari; Feroz Khan; Prem Narayan Yadav; Kapil Dev (Natural Product Research, 2025)

Widespread occurrence of Tilapia parvovirus in farmed Nile tilapia Oreochromis niloticus from India - Kooloth Valappil Rajendran; Neeraj Sood; B. Madhusudhana Rao; Anisha Valsalam; Megha K. Bedekar; Kezhedath Jeena; Pravata Kumar Pradhan; Anutosh Paria; Thangaraj Raja Swaminathan; Dev Kumar Verma; Naresh Kumar Sood (Journal of Fish Diseases, 2025)
Tilapia parvovirus (TiPV) has been associated with heavy mortalities in tilapia as a single infection or in co‐infection with Tilapia lake virus (TiLV). In this study, TiPV was detected in farmed Nile tilapia, Oreochromis niloticus , from two geographical regions of India, Maharashtra and Uttar Pradesh. TiPV‐specific polymerase chain reaction (PCR) reported earlier was used in the screening. Tilapia collected from Maharashtra showed characteristic clinical signs, and TiPV was detected along with TiLV and/or Aeromonas spp. However, fish from Uttar Pradesh were apparently healthy and only TiPV could be detected in these samples. A high prevalence of TiPV was recorded from both the geographical locations, Maharashtra and Uttar Pradesh (59.6% and 95.0% respectively). The virus could be detected in tissues such as the spleen, liver, kidney, brain and mucus. The spleen appeared to be the best tissue for detecting TiPV in apparently healthy tilapia. The presence of TiPV was further confirmed through sequencing the PCR products, isolation of the virus in the cell line and electron microscopy. Sequences of the NS1 gene of the two TiPV isolates showed similarity to the earlier reported TiPV isolates. The virus could be successfully propagated in O. niloticus Liver (OnL) cell line, and cytopathic effect was observed as early as 3 days post‐infection. Furthermore, the presence of non‐enveloped icosahedral to round virus particles measuring about 26–35 nm could be demonstrated in the cytoplasm and nucleus of infected OnL cells in transmission electron microscopy. With this confirmation of the presence of the virus, India is the third country to report TiPV after China and Thailand. The detection of TiPV in co‐infection cases with TiLV and in apparently healthy Nile tilapia suggests its wide distribution and potential synergistic effect in co‐infection cases. Therefore, this emerging virus needs holistic attention to understand its virulence, host‐specificity and epidemiological risk factors.

Establishment of a continuous cell line from heart of three spot gourami, Trichopodus trichopterus, a commercially important ornamental fish and its susceptibility to viruses - Aakriti Rastogi; Thangaraj Raja Swaminathan; Dev Kumar Verma; Hemant Kumar; Anutosh Paria; Pravata Kumar Pradhan; Uttam Kumar Sarkar; Neeraj Sood (Aquaculture, 2025)

Digital hemispherical photographs and Sentinel-2 multi-spectral imagery for mapping leaf area index at regional scale over a tropical deciduous forest - Mukunda Dev Behera; J. S. R. Krishna; Somnath Paramanik; Shubham Kumar; Soumit K. Behera; Sonik Anto; Shiv Naresh Singh; Anil Kumar Verma; Saroj K. Barik; Manas Ranjan Mohanta; Sudam Charan Sahu; Chockalingam Jeganathan; et al. (Tropical Ecology, 2024)

Susceptibility of selected tropical non-tilapine ornamental cichlids to Tilapia tilapinevirus following experimental infection - Anutosh Paria; Shrish C. Yadav; Dev Kumar Verma; Anup Mishra; Aakriti Rastogi; Ravindra; T.R. Swaminathan; K.V. Rajendran; Neeraj Sood; P.K. Pradhan (Aquaculture, 2023)

Phytocompounds of Rheum emodi, Thymus serpyllum, and Artemisia annua Inhibit Spike Protein of SARS-CoV-2 Binding to ACE2 Receptor: In Silico Approach - Rajan Rolta; Deeksha Salaria; PremPrakash Sharma; Bhanu Sharma; Vikas Kumar; Brijesh Rathi; Mansi Verma; Anuradha Sourirajan; David J. Baumler; Kamal Dev (Current Pharmacology Reports, 2021)